New geologic setting of Bekhme Formation - Karim, Kamal Haji (Sulaimani Journal for Pure and Applied Sciences, 2013)
Since the first description of Bekhme Formation (Late Campanian- Early Maastrichtian) by Wetzel in 1950 (in Bellen et al., 1959), no updating is published by later studies except confirmation of the first description. However, few published studied are deviated from the majorities and give serious suspicions about many parts of the previous description. The present study tries, on bases of stratigraphy, Correlation with Iran, fieldwork and paleontology, to evaluate these doubts and try to give evidence for abandoning this formation and changing it’s name to new formation (Perat Formation). Accordingly, it was proved that the top of Bekhme Formation is older than Late Campanian and it’s actual age is Turonian-Campanian. Additionally, it is concluded that the related basal conglomerate is choatic fault breccia. The changing of the name is based on the analysis of evidence of the previous studies, and introduction of new ones in which new stratigraphic column, stratigraphic positions and new depositional basin, tectonic and paleogeographic setting are proposed or established.
Keywords: Bekhme Formation; Kometan Formation; Aqra Formation; AqraBekhme Formation; Shiranish Formation